Copper removal from biological treatment system using modified adsorbent derived from groundwater treatment plant sludge and rice husk - Kutty, S.R.M. (Penerbit UTM Press, 2016)
Copper removal from synthetic wastewater by biomass assisted adsorbents was evaluated in this study. Three different biological reactors of the same size (8.5 L) were aerobically operated at solid retention time (SRT) of 30 days and hydraulic retention time (HRT) of 0.8 day. The first reactor was operated with biomass alone as the control reactor. The second reactor consist of biomass and ground water treatment plant sludge (GWTPS) whilst the third reactor consist of biomass and hybrid adsorbent (HA), which comprises 50 of microwaved incinerated rice husk ash (MIRHA) and 50 of GWTPS. The reactors were operated in eight different phases (Phase 1 â 8). Phases 1 â 2 were operated as acclimation period during which the biomass were allowed to stabilize within the reactor without copper addition. From phase 3 â phase 8, copper was added to the influent of the reactors at various concentrations and the reactor performance was monitored every two days. Results revealed that copper removal with the control reactor (RC) was markedly inferior compared with the reactors supported with GWTPS and HA adsorbents. The copper removal in the control reactor was in the range 0.47 â 2.62 mg/L from phase 5 to phase 8. Copper removal in the GWTPS reactor was in the range 0.19 â 0.83 mg/L from phase 5 to phase 8 whereas copper removal in the HA reactor was in the range 0.27 â 1.09 mg/L at the same conditions. Percentage removal of copper was 85 , 94 and 95 for the control, GWTPS and HA reactors, respectively. The adsorbents, GWTPS and HA reactors removed copper effectively. This study demonstrates that solid waste materials such as GWTPS and HA can be beneficially utilized to improve biomass tolerance towards heavy metal toxicity and yields a significant removal of copper. Â© 2016 Penerbit UTM Press. All rights reserved.